Efforts to Increase Students' Interest in Learning Islamic Education Subjects Through the Forum Group Discussion Strategy at SMA Muhammadiyah Purwodadi - Leoninda, Maysriva Wahyu; Abidin, Zaenal (FKIP - Universitas Riau, 2025)
Islamic Religious Education (PAI) is a form of learning provided by individuals or educational institutions to introduce and explore the teachings of Islam. Although it has great benefits in shaping students' morals and character, PAI is still often considered less interesting and not a priority for some students. Based on this, a learning strategy that can increase students' interest in Islamic Education is needed, one of which is the implementation of the Forum Group Discussion (FGD) strategy. This study aims to analyse the effectiveness of FGD strategy in increasing students' interest in learning at Muhammadiyah Purwodadi High School. This research uses descriptive analysis method with phenomenological approach. Data collection techniques were observation, interview, and documentation. The results showed that the implementation of FGD strategy was able to increase students' participation in PAI learning, especially in terms of courage to express opinions. However, the implementation of FGDs that have not been carried out routinely makes changes in students' interest in learning still limited. There are various challenges in its implementation, both from students and teachers themselves. Nevertheless, if this strategy is implemented more consistently with optimal assistance, FGD has the potential to be an effective method in increasing students' interest in learning.